Oxy-turbine for Power Plant with CO2 Capture. (July 2017) - Ferrari, Noemi; Mancuso, Luca; Davison, John; Chiesa, Paolo; Martelli, Emanuele; Romano, Matteo C.
Abstract: The IEA Greenhouse Gas R&D (IEAGHG) programme contracted Amec Foster Wheeler to perform a study providing an evaluation of the performance and costs of a number of oxy-turbine plants for utility scale power generation with CO2 capture. The main outcomes of the detailed technical and economical modelling of the most promising oxy-turbine cycles is presented in this paper, including sensitivity analyses on main technical and financial parameters. Each cycle configuration and optimization is developed jointly with the main cycle developers, i.e. Clean Energy Systems, Graz University of Technology and NET Power. The modelling of the gas turbine, including efficiency and blade cooling requirement, have been performed using a calculation code developed by Politecnico di Milano.